Kasus Kejahatan pada Anak Marak. Salah Siapa? (Analisis Penerapan Undang-Undang Perlindungan Anak) - Lihhiati Lihhiati (Syntax Idea)
Violence against children is still prevalent in the society. At the end of 2022, there were 16,106 cases of violence. It’s higher than the previous year which had 14,517 cases. Violence against children become a harsh reality for all of us because there are many children still living in the conditions that are far from feeling safe and comfortable. The right of the child to receive life protection and the ability to grow and develop themselves is fully guaranteed by the state. It’s legitimized in the 1945 constitution of Indonesia and regulated in Law No. 35 of 2014. The author interested in conducting analysis on the implementation of the child protection policy by using qualitative descriptive method. This interest is driven by the number of cases of violence against children which occur every year and are neither prevented nor minimized by the law. The author uses a literature study approach and conducts content analysis on data collected from news, journals, law, and websites related to the topic of this issue. As a result, apart from identifying several individual drivers or motivations, there are several factors that should be considered by all parties, especially the government, in terms of communication activities amidst the complexity of people's lives in the digital era.